Reconceptualizing the accountability of INGOs: From neo-institutional economic theory to an institutional logics approach - Alice Hengevoss (University of Basel, Center for Philanthropy Studies (CEPS), 2022)
International nongovernmental organizations (INGOs) face greater accountability demands from various stakeholders, and from their beneficiaries in particular. This has initiated an academic discourse on a more comprehensive approach to INGO accountability. However, the theoretical foundation to adequately conceptualize a comprehensive approach remains weak. This article takes the first step in establishing a theoretical foundation for researchers interested in further developing comprehensive INGO accountability. It does so by offering a systematic overview of the current academic discourse on INGO accountability. It then advances nine propositions on the implications of different theoretical approaches for the conceptualization of INGO accountability. In particular, it suggests that neo-institutional economic theories lead to a donor-focused and efficiency-oriented, and therefore narrow, conceptualization of INGO accountability. An institutional logics approach, on the other hand, allows conceptualizing INGO accountability relationships to a wider set of stakeholders, including to beneficiaries. It further allows developing an effectiveness-oriented conceptualization.
Keywords: 330; INGO accountability; nonprofit research; systematic literature review; neo-institutional theory; institutional logics